Synchrotron multimodal imaging in a whole cell reveals lipid droplet core organization. (8th May 2020) - Jamme, Frédéric; Cinquin, Bertrand; Gohon, Yann; Pereiro, Eva; Réfrégiers, Matthieu; Froissard, Marine
Abstract : Cryo soft X‐ray tomography and deep‐ultraviolet transmittance imaging reveal partitioning of neutral lipids in a lipid droplet core. Furthermore, deep‐ultraviolet transmittance and tryptophan/tyrosine auto‐fluorescence multimodal imaging on living cells were combined to obtain complementary information on organelle chemical contents. Abstract : A lipid droplet (LD) core of a cell consists mainly of neutral lipids, triacylglycerols and/or steryl esters (SEs). The structuration of these lipids inside the core is still under debate. Lipid segregation inside LDs has been observed but is sometimes suggested to be an artefact of LD isolation and chemical fixation. LD imaging in their native state and in unaltered cellular environments appears essential to overcome these possible technical pitfalls. Here, imaging techniques for ultrastructural study of native LDs in cellulo are provided and it is shown that LDs are organized structures. Cryo soft X‐ray tomography and deep‐ultraviolet (DUV) transmittance imaging are showing a partitioning of SEs at the periphery of the LD core. Furthermore, DUV transmittance and tryptophan/tyrosine auto‐fluorescence imaging on living cells are combined to obtain complementary information on cell chemical contents. This multimodal approach paves the way for a new label‐free organelle imaging technique in living cells.